Aquaporins with anion/monocarboxylate permeability: mechanisms, relevance for pathogen–host interactions - Rambow, Janis; Wu, Binghua; Rönfeldt, Deike; Beitz, Eric (Frontiers in Pharmacology, 2014)
Classically, aquaporins are divided based on pore selectivity into water specific, orthodox aquaporins and solute-facilitating aquaglyceroporins, which conduct e.g. glycerol and urea. However, more aquaporin-passing substrates have been identified over the years, such as the gases ammonia and carbon dioxide or the water-related hydrogen peroxide, and it became apparent that not all aquaporins clearly fit into one of only two subfamilies. Furthermore, certain aquaporins from both major subfamilies have been reported to conduct inorganic anions, such as chloride, or monoacids/monocarboxylates, such as lactic acid/lactate. Here, we summarize the findings on aquaporin anion transport, analyze the pore layout of such aquaporins in comparison to prototypical non-selective anion channels, monocarboxylate transporters, and formate-nitrite transporters, and discuss in which scenarios anion conducting aquaporins may be of physiological relevance.